THE CONSTRAINTS OF THE IMPLEMENTATION OF TEAM-BASED LEARNING IN CLASSROOM ACTION RESEARCH CLASS - Rusiana Rusiana (Vision: Journal for Language and Foreign Language Learning, 2016)
The previous research that I conducted, the use of Team-Based Learning in Classroom Action Research (CAR) class is well accepted and gives a good inﬂuence on the students’ learning. To have a responsibility to teach Action Research and to keep being reﬂective as a teacher, I am interested to implement TbL in anoth- er class of CAR which is aimed at knowing the constraints of its implementation and how the students cope with those constraints. The design of the research is qualitative research. The participants are one class of  Classroom Action Research class consists of  16 students. The instruments are observation and questionnaires. The ﬁndings show that the constraints on the implementation of TbL in CAR class are dealing with the material, team work, and incomplete team member. To cope with the constraints, the students have dis- cussion and ask for opinions among the team member. In addition, instead of discussion, to have complete team member is the pos- sible solution to cope with the constraints.